ICOST-IRI Integrasi Observasi Kelas Dan Tes Standar Dalam Evaluasi Pembelajaran Membaca Intensif Di Sekolah Dasar: Sebuah Pendekatan Mixed Methods: A Mixed Methods Approach - Dede Ginanjar; Yeni Yuniarti; Ai Sutini (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Intensive reading instruction plays a crucial role in developing elementary students’ basic literacy. However, its effectiveness is often inadequately evaluated due to limited instruments that capture both learning processes and outcomes. This study aims t o analyze the quality of intensive reading instruction through the integration of classroom observation and standardized tests as a holistic evaluation strategy. A mixed - methods approach with a convergent parallel design was employed, where qualitative and quantitative data were collected simultaneously, analyzed separately, and then integrated. Participants included 12 fifth - grade students and one teacher, selected through purposive sampling for the teacher and total sampling for students. Qualitative data were gathered via structured observations and semi - structured interviews, while quantitative data were obtained through standardized reading tests. Thematic analysis was used to identify patterns of interaction, reading strategies, and student engagement, while quantitative data were analyzed descriptively using averages and score distributions. The findings indicate that learning effectiveness is influenced by consistent reading strategies, clear objectives, and varied literacy activities. The integration of both data types provides a comprehensive and accurate evaluation of instructional quality, offering valuable insights for improving literacy practices in elementary education.